Development of Kupffer cell targeting type-I interferon for the treatment of hepatitis via inducing anti-inflammatory and immunomodulatory actions. (1st January 2018) - Minayoshi, Yuki; Maeda, Hitoshi; Yanagisawa, Hiroki; Hamasaki, Keisuke; Mizuta, Yuki; Nishida, Kento; Kinoshita, Ryo; Enoki, Yuki; Imafuku, Tadasi; Chuang, Victor Tuan Giam; Koga, Tomoaki; Fujiwara, Yukio; et al.
Abstract: Because of its multifaceted anti-inflammatory and immunomodulatory effects, delivering type-I interferon to Kupffer cells has the potential to function as a novel type of therapy for the treatment of various types of hepatitis. We report herein on the preparation of a Kupffer cell targeting type-I interferon, an albumin-IFNα2b fusion protein that contains highly mannosylated N-linked oligosaccharide chains, Man-HSA(D494N)-IFNα2b, attached by combining albumin fusion technology and site-directed mutagenesis. The presence of this unique oligosaccharide permits the protein to be efficiently, rapidly and preferentially distributed to Kupffer cells. Likewise IFNα2b, Man-HSA(D494N)-IFNα2b caused a significant induction in the mRNA levels of IL-10, IL-1Ra, PD-L1 in RAW264.7 cells and mouse isolated Kupffer cells, and these inductions were largely inhibited by blocking the interferon receptor. These data indicate that Man-HSA(D494N)-IFNα2b retained the biological activities of type-I interferon. Man-HSA(D494N)-IFNα2b significantly inhibited liver injury in Concanavalin A (Con-A)-induced hepatitis model mice, and consequently improved their survival rate. Moreover, the post-administration of Man-HSA(D494N)-IFNα2b at 2 h after the Con-A challenge also exerted hepato-protective effects. In conclusion, this proof-of-concept study demonstrates the therapeutic effectiveness and utility of Kupffer cell targeting type-I interferon against hepatitis via its anti-inflammatory and immunomodulatory actions.